CRITICAL THEMES IN DRAMA social, cultural and political analysis. - Freebody, Kelly ([S.l.] : ROUTLEDGE, 2021)
Critical Themes in Drama is concerned with the relationship between drama and the current socio-political context. It builds on and contributes to ongoing scholarly conversations regarding the use, benefit, challenges and opportunities for drama and theatre as a social, cultural, educational and political act. The intention of this book is to canvas current theory and practice in drama, to provide an extended examination of how drama as a pro-social practice intersects with socio-cultural institutions, to link critical discourse and examine ways drama may contribute to a broader social justice agenda. Authors draw on a variety of theoretical tools from the fields of sociology, anthropology and cultural studies. This combines with an exploration of work from drama practitioners across a variety of countries and practices to provide a map of how the field is shaped and how we might understand drama praxis as a social, cultural and political force for change. This book offers drama scholars, practitioners, researchers and teachers a critical exploration which is both hopeful and critical; acknowledging the complexities and potential pitfalls, while celebrating the opportunities for drama as a practice for social action and positive change.
Framing the drama of these times. Chapter 1: Introduction to the drama of these times. Chapter 2: Enduring Inequity. Chapter 3: Useful drama in neoliberal times. Chapter 4: Dramatic democracy. Chapter 5: Creativity and the Global Education Reform Movement. Examining the drama of these times. Chapter 6: Glocalisation: Mythologising place and community. Chapter 7: Migration -- Dramatic Comings and Goings. Chapter 8: The theatre of battle. Chapter 9: The drama of sex and sexuality. Chapter 10: The health and happiness project: being 'well' in these times. Preparing for drama of future times. Chapter 11: Climate change -- a battle for our hearts and minds. Chapter 12: Digital+ destinies. Chapter 13: Imagining and acting in the extended present for unthought futures. Chapter 14: The future looks bright?. Chapter 15: Enduring discourses of beauty, love and hope
OCLC-licensed vendor bibliographic record.
Keywords: Theater and society; Theater -- Political aspects; Social action; EDUCATION / General